For $a\ge \frac{1}{8}$, we define, $$g(a)=\sqrt[\Large3]{a+\frac{a+1}{3}\sqrt{\frac{8a-1}{3}}}+\sqrt[\Large3]{a-\frac{a+1}{3}\sqrt{\frac{8a-1}{3}}}$$

Find the maximum value of $g(a)$.

I came across this question in a Math Olympiad Competition and I am not sure how to solve it. Can anyone help? Thanks.

  • $\begingroup$ I've made an edeit to your post. I believe this is what you ment? If not correct me.... $\endgroup$ – gebruiker Jun 6 '14 at 13:52
  • $\begingroup$ Due to the complexity of the equation(hard to type), I decided to use an image instead. $\endgroup$ – snivysteel Jun 6 '14 at 13:53
  • $\begingroup$ Very smart. I'll try to get is fixed based on the image... $\endgroup$ – gebruiker Jun 6 '14 at 13:53
  • $\begingroup$ I fixed it, the image was a little hard to decipher, is it ok now? $\endgroup$ – Pranav Arora Jun 6 '14 at 13:55
  • $\begingroup$ Yeah, thanks for your help! $\endgroup$ – snivysteel Jun 6 '14 at 13:58

In general we cannot rewrite a cubic radical in a simple way. However both radicals in $g(a)$ are of a special form that can be denested, because we can find two cubic powers $X^3,Y^3$ such that $X, Y $ are quadratic conjugate irrationals and

\begin{equation*} a+\frac{a+1}{3}\sqrt{\frac{8a-1}{3}}=X^{3},\qquad a-\frac{a+1}{3}\sqrt{\frac{ 8a-1}{3}}=Y^{3}. \end{equation*}

If we write $x=\frac{8a-1}{3}\geq 0$, then $a=\frac{3x+1}{8}$ and $\frac{a+1 }{3}=\frac{x+3}{8}$. Consequently, the first radicand becomes

\begin{eqnarray*} a+\frac{a+1}{3}\sqrt{\frac{8a-1}{3}} &=&\frac{3x+1+\left( x+3\right) \sqrt{x} }{8}=\frac{1+3\sqrt{x}+3x+\left( \sqrt{x}\right) ^{3}}{8} \\ &=&\frac{\left( 1+\sqrt{x}\right) ^{3}}{2^{3}}=X^{3},\qquad X=\frac{ 1+\sqrt{x} }{2}=\frac {1}{2}+\frac {1}{2}\sqrt {\frac {8a-1}{3}}, \end{eqnarray*}

where we used the binomial theorem for the cubic power

\begin{equation*} \left( 1+c\right) ^{3}=1+3c+3c^{2}+c^{3}, \end{equation*}

with $c=\sqrt{x}$:

\begin{eqnarray*} \left( 1+\sqrt{x}\right) ^{3} &=&\left( 1+x^{1/2}\right) ^{3}=1+3x^{1/2}+3x+x^{3/2} \\ &=&1+3\sqrt{x}+3x+\left( \sqrt{x}\right) ^{3}. \end{eqnarray*}

Similarly, using the binomial theorem for $(1-c)^3=(1-\sqrt{x})^3$, the second radical becomes

\begin{eqnarray*} a-\frac{a+1}{3}\sqrt{\frac{8a-1}{3}} &=&\frac{3x+1-\left( x+3\right) \sqrt{x} }{8}=\frac{ 1-3\sqrt{x}+3x-\left( \sqrt{x}\right) ^{3}}{2^{3}} \\ &=&\frac{\left( 1-\sqrt{x}\right) ^{3}}{2^{3}}=Y^{3},\qquad Y=\frac{ 1-\sqrt{x} }{2}=\frac {1}{2}-\frac {1}{2}\sqrt {\frac {8a-1}{3}}. \end{eqnarray*}

Now we find easily that for $a\geq 1/8$ the function $g(a)$ is constant

\begin{equation*} g(a)=\sqrt[3]{X^{3}}+\sqrt[3]{Y^{3}}=X+Y=\frac{ 1+\sqrt{x} }{2} +\frac{ 1-\sqrt{x} }{2} =1. \end{equation*}

Hence $\max_{a\geq 1/8}g(a)=1.$


Hint: Let $u =\sqrt{\frac{8a-1}{3}}$ which implies $a = \frac{3u^2+1}{8}$. Then you have to find the max of \begin{align*} \sqrt[3]{\frac{3u^2+1+u^3+3u}{8}}+\sqrt[3]{\frac{3u^2+1-u^3-3u}{8}}. \end{align*} Observe the expansions of $(1+u)^3$ and $(1-u)^3$.


Note the $$(a+b)^3=a^3+b^3+3ab(a+b)$$ so $$g^3(a)=2a+3\sqrt[3]{a^2-\dfrac{(a+1)^2}{9}\cdot\dfrac{8a-1}{3}}\cdot g(a)$$

  • 2
    $\begingroup$ How would you continue? $\endgroup$ – Calvin Lin Jun 6 '14 at 14:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.